Effect Of Third Party Funds On Lending To National Private Commercial Banks - Didin Rasyidin Wahyu; Herna Setiawati (Journal of Applied Business, Taxation and Economics Research, 2022)
: This study aims to determine whether there is an influence between the independent variables (Current Accounts, Savings, and Deposits) on the dependent variable (Credit Distribution) at the National Private Commercial Banks listed on the Indonesia Stock Exchange (IDX) for the period 2014-2019. The research method used in this study is a quantitative method, the sample used in this study is a national private public banking company, a total of 7 national private banking companies are determined as a sample, the sampling technique is done using the Purposive Sampling method . The data used are secondary data in the form of company financial statements, analysis using Multiple Linear Regression analysis. The results showed that partially there is an influence of Demand Deposits on Credit Distribution, there is an effect of Savings on Credit Distribution and there is an influence of Deposits on Credit Distribution. While simultaneously (together) there is the influence of Demand Deposits, Savings, and Deposits on Credit Distribution. there is an effect of Savings on Credit Distribution and there is an influence of Deposits on Credit Distribution. While simultaneously (together) there is the influence of Demand Deposits, Savings, and Deposits on Credit Distribution. there is an effect of Savings on Credit Distribution and there is an influence of Deposits on Credit Distribution. While simultaneously (together) there is the influence of Demand Deposits, Savings, and Deposits on Credit Distribution.